Evidence of the presence of opticlike collective modes in a liquid from neutron scattering experiments. - Bermejo, F; Taylor, J; McLain, SE; Bustinduy, I; Turner, J; Ruiz-Martin, MD; Cabrillo, C; Fernandez-Perea, R (2006)
Inelastic neutron scattering data from liquid DF close to the melting point show, in addition to spectra comprising quasielastic and heavily damped acoustic motions, an intense, nondispersive band centered at about 27 meV along with a broader higher energy feature. Observation of the former band provides the first direct verification of the existence within the liquid state of collective opticlike excitations as predicted by molecular dynamics simulations. The latter corresponds to mainly reorientational motions assigned from mode eigenvector analysis carried out by computer simulations.